Pemanfaatan Kulit Semangka Menjadi Manisan Guna Menjaga Ketahanan Pangan di Kecamatan Puger Kabupaten Jember - Ferdiansyah Putra Manggala; Karina Nine Amalia; Tri Agustina Nugrahani (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2025)
This study explores the potentian of watermelon rind processing into sweets as an innovative solution in managing organic waste and improving economic welfare in Mojosari Village, Jember Regency. With a total population of 9.470 people, this village relies on the agricultural sector, where watermelon rind is a waste that is often overlooked. This study identifies the volume of waste, current management practices, and evaluates the environmental impacts and economic benefits of watermelon rind processing. Research methods include surveys, interviews, and observations, followed by watermelon rind processing into sweets. The results show that this processing not only reduces the environmental ipmpact of waste but also opens up new economic opportunities for farmers and farm laborers. Implementation of this model has the potential to improve food security by strengthening local food production systems and reducing dependence on foreign food ingirdients. Recommendations include wide-scale implementation an training for communities on processing techniques an tehir benefits.